Political Correspondence And Public Pressure: Study Of Environmental And Water Performance - Fidiana Fidiana (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to examine public pressure and political correspondence on environmental and water disclosures. Specifically, based upon a panel dataset of 114 Indonesian listed firms operating in highly risk water industries (Miscellaneous Industry, Basic Industry, Consumer Goods Industry, Agriculture, and Mining) during 2017–2019, we use regression models to analyze the relationships between water disclosure based on the GRI 300 (environmental) and 303 (water) guidelines and public pressure and political-connected firms. Our empirical results show the positive influence of public pressure and environmental and water disclosure. Meanwhile, political correspondence has no bearing on water-related disclosures, implying that every firm undertakes the disclosure without regard for political ties. The digital era has changed the supervisory mechanism to be tighter so that each issuer cannot take shelter in political ties to ignore their business responsibilities. The results of this study have important policy implication, particularly regarding the commitment to water-related reporting, the amount of disclosure remains low, which could be due to a lack of demand from stakeholders or a lack of need for water reporting to provide legitimacy. This suggests that firms will enhance their water commitment using GRI standards and disclose more detailed in financial statements.